Design and functional characterization of synthetic E3 ubiquitin ligases for targeted protein depletion: Selective protein knockout using engineered ubiquibodies - Baltz, Morgan R. (Curr Protoc Chem Biol, 2018)
A number of techniques now exist for decreasing the expression of cellular proteins without the need for genomic modification. One such technique involves engineered protein chimeras that combine the ubiquitination activity of E3 ubiquitin ligases with the binding affinity and substrate specificity of designer binding proteins (DBPs). These chimeras, called “ubiquibodies”, are capable of selectively and controllably steering virtually any protein to the ubiquitin proteasome pathway (UPP) for degradation, making ubiquibodies a powerful addition to the protein knockout toolbox. A distinguishing feature of ubiquibodies is their modularity – simply swapping DBPs can generate a new ubiquibody with specificity for a different substrate protein. Moreover, by employing DBPs that recognize particular protein states (e.g., active vs. inactive conformation, mutant vs. wildtype, post-translational modification), it becomes possible to deplete certain protein subpopulations while sparing others. This protocol outlines the steps necessary to design and functionally evaluate ubiquibodies for customizable silencing of cellular proteins.